Energy sources and global sustainability connectedness: Evidence from green and dirty energy - Samet Gunay; Selma Kurtishi-Kastrati; Mohamed Sraieb; Gadaf Rexhepi (Sustainable Futures, 2025)
The type and efficiency of energy are crucial for achieving global sustainability goals. To empirically explore this relationship and provide valuable insights for various market stakeholders, this study analyzes the connectedness between global sustainability and green and dirty energy sources using Time and Frequency Domain Connectedness Analysis. Global sustainability (GSI), green energy (GEI), and dirty energy (DEI) are represented by the Nasdaq Future Global Sustainability Leaders Index, Nasdaq Clean Edge Green Energy Total Return Index, and Vanguard Energy Exchange-Traded Fund, respectively. The results show that, on average, 35.61 % of the forecast error variance spillovers of GSI can be attributed to green and dirty energy indices. Across all frequencies, GEI has a significantly greater influence than DEI in explaining forecast variance spillovers of GSI, as indicated by both static and pairwise dynamic directional connectedness analyses. These findings suggest that the relationship between global sustainability and green energy remains fragile, driven by short-term market dynamics often influenced by speculation and sentiment. Policymakers should implement stronger, more consistent policies to foster stable, long-term connections led by the green energy market, incentivizing entrepreneurs to invest in this sector and promoting sustainability.